2000
DOI: 10.1051/rnd:2000128
|View full text |Cite
|
Sign up to set email alerts
|

LH release in mink (Mustela vison). Pattern of the LH surge and effect of metabolic status

Abstract: -The mink is a seasonal breeder with induced ovulation and delayed implantation. Reproductive processes are strongly influenced by energy supply and body condition. Items for which there is paucity or complete lack of data were the main objectives of this study: the temporal relationship between copulation and the pre-ovulatory LH surge and the influence of energy supply on LH release. A total of 30 yearling female mink with a well defined metabolic status was used. Twelve females kept in the laboratory were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…We previously demonstrated a high correlation between plasma insulin and leptin in non-pregnant mink dams and during GEST1/3 (r 0•75, P, 0•001; Tauson & Forsberg, 2002). However, because insulin concentrations declined in late gestation when food intake was low, which is in accordance with previous findings in mink demonstrating a close relationship between food intake and plasma insulin (Fink & Tauson, 1998;Fink et al 1998;Tauson et al 2000), the hyperleptinaemia found in the present study could not be explained by the stimulation by high insulin concentrations. Oestrogen seems more likely to have exerted stimulation because high concentrations of oestradiol-17b occur during the late part of gestation in mink (Tauson, 1991).…”
Section: Discussionsupporting
confidence: 89%
“…We previously demonstrated a high correlation between plasma insulin and leptin in non-pregnant mink dams and during GEST1/3 (r 0•75, P, 0•001; Tauson & Forsberg, 2002). However, because insulin concentrations declined in late gestation when food intake was low, which is in accordance with previous findings in mink demonstrating a close relationship between food intake and plasma insulin (Fink & Tauson, 1998;Fink et al 1998;Tauson et al 2000), the hyperleptinaemia found in the present study could not be explained by the stimulation by high insulin concentrations. Oestrogen seems more likely to have exerted stimulation because high concentrations of oestradiol-17b occur during the late part of gestation in mink (Tauson, 1991).…”
Section: Discussionsupporting
confidence: 89%
“…Our observations confirm the previous reports ( Sundqvist et al, 1989 ; Tauson et al, 2000 ) of the release of steroid hormones progesterone and estradiol by mink ovaries. These hormones are considered important regulators of reproduction in this ( Tauson et al, 2000 ; Tauson, 2001 ) and other ( Sirotkin, 2014 ) species. The age-dependent changes in the release of progesterone and estradiol and their response to leptin and IGF-I provide the first evidence that these hormones are involved in the control of mink reproductive aging.…”
Section: Resultssupporting
confidence: 93%
“…The farm breeding of these fur animals is important from an economical viewpoint, but the hormonal control of mink reproduction is insufficiently studied ( Sundqvist et al, 1989 ; Amstislavsky et al, 2008 ). The release and involvement of several hormones (including progesterone, estradiol and IGF-I) in the control of mink reproduction have been reported ( Sundqvist et al, 1989 ; Tauson et al, 2000 ; Tauson, 2001 ). Nevertheless, the role of leptin and IGF-I in the control of mink ovarian hormones release has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduction in mink is strictly regulated by photoperiod and reproductive outcome is very responsive to nutritional manipulation (Tauson, 2001). In extremely lean animals the pre-ovulatory luteinizing hormone surge and ovulation can be abolished (Tauson et al 2000). None of the mated females was in such a lean condition at mating, but the female remaining barren had been in such condition by the end of the restriction period.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that insulin changes rapidly in mink in response to changes in energy supply (Fink et al 1998;Tauson et al 2000), which was confirmed here and fits the concept of insulin as regulator of energy-supply-induced changes in leptin secretion (Havel, 2000). However, food restriction may cause an increased sympathetic activity to the white adipose tissue (Migliorini et al 1997), and this regulation mediated via catecholamines and b-agonists seems to be more pronounced than other regulatory factors , so it cannot be excluded that this mechanism was the main cause of the decrease in plasma leptin during food restriction.…”
Section: Discussionmentioning
confidence: 99%